Detection of Herpes Simplex Virus DNA by Real-Time PCR - Kessler, Harald H. (American Society for Microbiology, 2000)
Molecular detection of herpes simplex virus (HSV) DNA is recognized as the reference standard assay method for the sensitive and specific diagnosis of central nervous system infections caused by HSV. In this study, a molecular assay based on real-time PCR on the LightCycler (LC) instrument was evaluated and compared with a home-brew molecular assay. The detection limit of the LC assay was determined with 10-fold dilutions of plasmid pS4 with the SalI restriction fragment of the DNA polymerase gene and with the First European Union Concerted Action HSV Proficiency Panel. A total of 59 cerebrospinal fluid (CSF) specimens were investigated for the comparative study. With plasmid pS4, the detection limit of the LC assay was found to be 10(4) copies per ml, i.e., 12.5 copies per run. When samples of the First European Union Concerted Action HSV Proficiency Panel were tested, 2 × 10(3) to 5 × 10(3) HSV type 1 genome equivalents (GE) per ml, i.e., 2.5 to 6.3 GE per run, could consistently be detected. There was a correlation between the LC assay and the home-brew assay in 55 of 59 specimens. In conclusion, the LC assay allows very rapid detection of HSV DNA in CSF. It was found to be laborsaving and showed sufficient sensitivity.